The prediction of pregnancy induced hypertension from umbilical and uterine Doppler flow study - Gadhavi, Vijay N.; Gadhavi, Mansi K.; Pandya, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorder along with hemorrhage and infection contribute greatly to maternal mortality and morbidity. Pregnancy induced hypertension remains among the most significant and intriguing unsolved problems in obstetrics. Methods: In this prospective analytical study investigations and color doppler findings 0f umbilical artery PI, RI and end diastolic flow in same, uterine PI, RI and persistent diastolic notch in uterine artery recorded. Total 100 Cases of PIH between 20-36 weeks of gestation in 2 years with B.P ≥ 140/90 mm hg and protienuria ≥ 1+ were observed. Results: In this study, out of 100 cases, there were 58 cases of mild PIH (58%) and 42 cases of severe PIH (42%). Umbilical artery PI was elevated in 43(43.0%) patients and was normal in 57(57.0%) patients. Umbilical artery RI was more than and equal to 0.7 in 77 patients (77%) and was below of 0.7 in 23 (23%) pa-tients.9(9.0%) fetuses showed absence and 14 (14.0%) fetus had reversal and 46 (46.0%) had reduced end diastolic umbilical artery flow with total 69 out of 100 fetuses having abnormal waveforms.65 (65%) mothers had an elevated uterine artery PI and 35(35%) patients had normal uterine artery PI. in observation 69 (69%) patients were having RI more than 0.6, while 31 (31%) were having less than 0.6 out of 100 patients. In this study, 65 (65.0%) women were having persistent diastolic notch. Conclusions: This study was to evaluate arterial flow velocities as a predictor of impending pregnancy induced hypertension with raised RI and PI along with umbilical ab-sent or reverse end diastolic flow velocities and elevated RI and PI in the presence of a diastolic notch are considered as abnormal uterine doppler findings doppler finding with unfavorable outcome.